2022
DOI: 10.3389/fimmu.2022.873982
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3a Enhances the Phagocytic Activity of B Cells Through C3aR in a Fish

Abstract: The complement system is an important part of the immune system of teleost fish. Besides, teleost B cells possess both phagocytic activity and adaptive humoral immune function, unlike mammalian B1 cells with phagocytic activity and B2 cells specific to adaptive humoral immunity. However, the cross talk between complement system and phagocytic B cells in teleost fish still requires elucidation. Here, we show that, unlike tetrapods with a single C3 gene, nine C3 genes were identified from the grass carp (Ctenoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Phagocytes are also the first line of defense in the innate immunity of bony fishes. Recent studies pointed out that C3a enhances the phagocytic activity of B cells through C3aR in grass carp [ 24 , 37 ]. The fragments of C3, such as C3b and iC3b, are extremely important in the complement system for opsonophagocytosis [ 15 , 16 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phagocytes are also the first line of defense in the innate immunity of bony fishes. Recent studies pointed out that C3a enhances the phagocytic activity of B cells through C3aR in grass carp [ 24 , 37 ]. The fragments of C3, such as C3b and iC3b, are extremely important in the complement system for opsonophagocytosis [ 15 , 16 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sequence information and functions of C3 have been successfully characterized in several bony fishes including the grass carp ( Ctenopharyngodon idella ) [ 24 , 25 ], Japanese flounder ( Paralichthys olivaceus ) [ 26 ], large yellow croaker ( Larimichthys crocea ) [ 27 ], dojo loach ( Misgurnus anguillicaudatus ) [ 28 ], and rainbow trout ( Oncorhynchus mykiss ) [ 29 ]. In grass carp, complement C3 is involved in the process of resisting A. hydrophila and repairing tissue damage caused by bacterial infection [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the results of this study indicated that bafetinib, a Lyn inhibitor (Lazarian et al ., 2021; Pauls et al ., 2016; Zhang et al ., 2021), had slightly decreased the phagocytosis activity of B cells to N. seriolae (Figure 7b,d). Nonetheless, besides FcRs, the B‐cell receptor complex (Wu et al ., 2019a; Wu et al ., 2019b) and the complement receptors (Li et al ., 2007; Ma et al ., 2022) exerted regulatory effects on the phagocytic activity of B cells. Thus, the inhibitory effect of only one of them might be inconspicuous.…”
Section: Discussionmentioning
confidence: 99%